ENSO (EL NIÑO-SOUTHERN OSCILLATION) INFLUENCE ON WIND AND WAVE VARIABILITY IN MALUKU WATERS - Johannis Steven Helmus Kakiailatu; Julius AN Masrikat; Simon Tubalawony (Universitas Mataram, 2024)
Maluku waters are among the waters in Indonesia that have a strategic location. Maluku waters encompass several seas with different characteristics, including the Banda Sea, Seram Sea, and Arafura Sea. One phenomenon that affects atmospheric conditions and Maluku waters is ENSO. The influence of ENSO on wind and wave variability in Maluku waters is the purpose of this study. This study uses ONI Index data, as well as wind and wave data from BMKG-OFS products that have a spatial resolution of 7 km and a temporal resolution of 3 hours. The ENSO neutral period occurred throughout 2013, El Nino in 2015, and La Nina in 2022. The results showed that ENSO affects wind and wave intensity. In January, the winds range between from 2 to 20 knots and moved predominantly from northwest to southeast. In February, it appears that only the El Nino period has a large enough range. In July, the maximum wind range is up to 25 knots, moving predominantly from the southeast towards the northwest. The La Nina period strengthens wave intensity, in January with a range of 0 to 1.5 meters. In July, the wave intensity is higher during the La Nina period, with wave heights reaching 3 meters. The El Nino period strengthens wind intensity, while La Nina strengthens wave intensity in Maluku waters.